Lake Baikal : a mirror in time and space for understanding global change processes : the 1998 BBD Baikal Symposium of the Japanese Association for Baikal International Research Program (JABIRP), Yokohama, November 5th-8th, 1998 - Minoura, Kōji.; ScienceDirect eBooks (Amsterdam ; London ; New York : Elsevier, 2000)
Lake Baikal is the oldest lake and largest freshwater reservoir in the world. As a result of its exceptionally long geological history, the lake has been a theatre of evolution and speciation of organisms, and it currently harbors more species than any other lake in the world. Based on its unique nature, Lake Baikal was recently designated a World Heritage site and is regarded as a hotspot for evolution, speciation, and biodiversity. With its tremendously peculiar biota, Lake Baikal is now awaiting modern analytical approaches to the profound problems of speciation and evolution. In late autumn 1998 a symposium was held in Japan with the theme "Lake Baikal: A mirror in time and space for understanding global change processes" to bring together scientists from different disciplines who are studying Lake Baikal. Three international scientific associations: The BICER (Baikal International Center for Ecological Research), BDP (Baikal Drilling Project), and DIWPA (Diversitas Western Pacific and Asia) were involved in the organisation. This book contains a selection of papers presented at this symposium. They are interdisciplinary in nature and bring together results from geology, paleontology, chemistry, biology, limnology and physics.
Cover -- Table of Contents -- Preface -- Introduction -- Part 1: Paleoenvironment and Rift Basin History -- Chapter 1. Baikal drilling project -- Chapter 2. Changes in the Lake Baikal levels and runoff direction in the Quaternary period -- Chapter 3. Paleomagnetic and rock-magnetic studies on Lake Baikal sediments: BDP 96 borehole at Academician Ridge -- Chapter 4. Paleoclimatic signals printed in Lake Baikal sediments -- Chapter 5. Glaciations of central Asia in the late Cenosoic according to the sedimentary record from Lake Baikal -- Chapter 6. Palaeoclimatic changes from 3.6 to 2.2 Ma B.P.derived from palynological studies on Lake Baikal sediments. -- Chapter 7. TEM analysis of smectite-illite mixed-layer minerals of core BDP 96 Hole 1 : Preliminary results -- Chapter 8. Forest-desert alternation history revealed by pollen- record in Lake Baikal over the past 5 million years -- Chapter 9. Vegetation history of the southeastern and eastern coasts of Lake Baikal from bog sediments since the last interstade -- Chapter 10. Estimation of paleoenvironmental changes in the Eurasian continental interior during the past 5 million years inferred from organic components in the BDP96 Hole 1 sediment core from Lake Baikal -- Chapter 11. Paleoenvironmental change in the Eurasian continent interior inferred from chemical elements in sediment cores (BDP96/1, BDP96/2) from Lake Baikal -- Chapter 12. A new preparation method for qualitative and quantitative analysis of fossil sponge spicules by light microscope -- Chapter 13. Evolution of freshwater centric diatoms within the Baikal rift zone during the late Cenozoic -- Part 2: Physicochemical Limnology -- Chapter 14. Elemental composition of short sediment cores and ferromanganese concretions from Lake Baikal -- Chapter 15. Mercury distribution in the bottom and stream sediments of Lake Baikal, water reservoirs of the Angara river cascade, and the adjacent drainage basins -- Chapter 16. Correlation between geochemical features of recent bottom and stream sediments in the Baikal geoecological polygon -- Chapter 17. Remote sensing methods in studies of Lake Baikal environment -- Chapter 18. Environmental impact on the dynamics of Lake Baikal phytoplankton taxanomic groups: modeling attempt -- Chapter 19. Nonlinear stability near the temperature of maximum density and thermobaric instability in Lake Baikal during summer stratification -- Chapter 20. Study of the elemental composition of suspended particles in large continental lakes (Baikal and Khubsgul) -- Chapter 21. Atmospheric and riverine input of nutrients and organic matter into Lake Baikal -- Chapter 22. Comparison of persistent organochlorine pollutant behavior in the food webs of Lakes Baikal and Superior -- Chapter 23. Carbon and nitrogen isotope studies of pelagic ecosystem and environmental fluctuations of Lake Baikal -- Chapter 24. Some speculations on the possibility of changes in deep-water renewal in Lake Baikal and their consequences -- Chapter 25. Contamination of the ecosystems of Lake Baikal by persistent organochlorines -- Part 3: Evolution and Biodiversity -- Chapter 26. Genetic differentiation of gammarid (Eufimnogammarus cyaneus) populations in relation to past environmental changes in Lake Baikal -- Chapter 27. Myological peculiarities of the comephoridae: an endemic fish taxon of Lake Baikal (Pisces: Teleostei) -- Chapter 28. Morphometric comparison of skulls of seals of the subgenus Pusa -- Chapter 29. The importance of habitat stability for the prevalence of sexual reproduction.
Revised conference proceedings.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Ecology -- Russia (Federation) -- Baikal, Lake -- Congresses; Limnology -- Russia (Federation) -- Baikal, Lake -- Congresses; Baikal, Lake (Russia); SCIENCE -- Environmental Science (see also Chemistry -- Environmental); NATURE -- Ecosystems & Habitats -- Wilderness; NATURE -- Ecology; SCIENCE -- Life Sciences -- Ecology; Ecology; Limnology; Russia (Federation) -- Lake Baikal; Electronic books